2020
DOI: 10.3389/fvets.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey on Vector-Borne Pathogens in Alpine Wild Carnivorans

Abstract: In Europe, free-ranging wildlife has been linked to the emergence of several vector-borne diseases such as rodents for Borrelia burgdorferi s.l. In particular, wild carnivorans are one of the most important sources of emerging zoonotic pathogens worldwide, although little information is available regarding the epidemiology of vector-borne parasites in these animals. Thus, the aim of this paper was to investigate the prevalence of Babesia spp., Anaplasma spp., Ehrlichia spp., Hepatozoon spp. and Leishmania infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
136
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 77 publications
8
136
5
Order By: Relevance
“…Although not directly comparable, present results about ProQoL are consistent with previous results indicating that veterinarians score higher on compassion satisfaction than on dimensions linking to compassion fatigue [29,109,111]. As concerns demographic variables, according to other studies [10,15], SEM results showed that females reported a higher risk of experiencing negative outcomes, such as compassion fatigue and burnout.…”
Section: Plos Onesupporting
confidence: 89%
“…Although not directly comparable, present results about ProQoL are consistent with previous results indicating that veterinarians score higher on compassion satisfaction than on dimensions linking to compassion fatigue [29,109,111]. As concerns demographic variables, according to other studies [10,15], SEM results showed that females reported a higher risk of experiencing negative outcomes, such as compassion fatigue and burnout.…”
Section: Plos Onesupporting
confidence: 89%
“…infections are both found in domestic animals and wildlife in Great Britain and A. phagocytophilum was detected in 0.74% of ixodid ticks collected from British dogs [37]. However, as in this study, A. phagocytophilum was not detected in badgers in The Netherlands, Czech Republic, and Spain and only a low prevalence was observed among badgers in another study conducted in Belgium and The Netherlands, as well as in Italy, suggesting badgers do not play a significant epidemiological role in this infection ( [32] and references therein). A previous survey found what appeared to be a novel Bartonella sp., most closely related to B. clarridgeiae, in 12% of badgers in northern Spain [38].…”
Section: Discussioncontrasting
confidence: 44%
“…A novel Ehrlichia sp. was found in a badger in Northern Spain [31] and isolates recently obtained from Italian badgers showed 99% similarity with it [32]. C. burnetii infection is endemic in British livestock, and seropositivity is common in people working with them.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations